An Analysis of the Gap Between Targets and Achievements in the Implementation of Renewable Energy Policy in Indonesia - Adityo Sumaryadi; Amy Yayuk Sri Rahayu (Eduvest - Journal of Universal Studies, 2026)
Indonesia has set a target for the New and Renewable Energy (NRE) mix of 23% as part of the national energy transition strategy, but its realization is still far below the target. This study aims to analyze the gap between the targets and achievements of the NRE mix in Indonesia using the Implementation Gap Theory from Pressman and Wildavsky. This study uses a qualitative approach with a descriptive method. The results of the study show that the gap between NRE achievements and targets due to the failure of policy implementation is structural and systemic, which is reflected in the disparity in fiscal incentives that still favor fossil energy, limited administrative capacity, policy design that is insufficiently operational, and a high administrative burden in the implementation process. The gap in the NRE mix is the result of accumulated implementation failures at various points in the policy chain, so strengthening implementation capacity and the alignment of policy incentives is the key to narrowing the gap between NRE targets and achievements in Indonesia.